Сравнительный анализ планарной и пространственной аксиальной трёхфазных электромагнитных систем с параллельными образующими поверхностями стержней и обмоточных окон (массостоимостные показатели) - Авдеева, Е.А. (Електротехніка і електромеханіка, 2012)
Analytical dependences of optimum geometrical relationship determination with criteria of minimal weight and price of the active part are obtained. Comparative analysis of mass and price indexes of planar and spatial three-phase electromagnetic systems with rectangular and sector forming contours of the cores, yokes and winding coils is made.